THE EFFECT OF TAXPAYER AUDITS, TAX FAIRNESS AND ECONOMIC MOTIVES ON TAX EVASION - Indah Yani , Mega Sari; Marlina , Evi; Mustika Putri , Annie (LP2M IBK Nitro, 2025)
This study aims to examine the influence of tax audits, tax fairness, and economic motives on tax evasion among individual taxpayers. The background of this study is based on the still high practice of tax evasion which has a negative impact on state revenue. This study uses a quantitative approach with a survey method of 100 respondents registered at the Pekanbaru Senapelan Pratama Tax Office. Data analysis was conducted using multiple linear regression using SPSS version 25. The results show that tax audits and economic motives have a significant effect on tax evasion, while tax fairness does not show a significant effect. This study contributes to the development of fiscal policy, particularly in improving the effectiveness of supervision and understanding of taxpayers' economic motivations in order to minimize evasion practices